Peningkatan Hasil Padi di Tanah Sulfat Masam melalui Kombinasi Perlakuan Lindi dan Olah Tanah - Ar-Riza, Isdijanto; Alwi, M.; ,, Nurita (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACT Tidal swamp lands containing acid sulphate is easily become idle land, which can be fixed by reducing oxidation process of pyrite (FeS2). The pyrite oxidation causes disturbance on the growth and yield of rice plant. An experiment was conducted by means soil leaching in order to reduce accumulation of pyrites. The research had been conducted in Simpang Jaya village, Barito Kuala District in 2012 using a split plot design with three replications. As the main plot was leaching, and no leaching treatment, while as the subplot was soil tillage, i.e., 1) control, 2) weeds cleared without tillage, 3) soil tillage at a depth of 15 cm, and 4) soil tillage at a depth of 30 cm. The results showed that the leaching treatment combined with tillage at a depth of 15 cm or 30 cm increased the number of rice tillers, shoot dry weight, and number of panicles per hill, and number of seeds per hill, thus the leaching treatment was able to increase rice production.Keywords: acid sulphate, leaching, pyrite, tidal swamp land